Oral Health Care of Children and Adolescents with Different Impairments of Cerebral Palsy: Barriers and Challenges - Elizabeth Louisy Marques Soares da Silva-Selva; Paulo Cardoso Lins-Filho; Thuanny Silva de Macêdo; Jaciel Leandro de Melo Freitas; Camilla Siqueira de Aguiar; Márcia Maria Vendiciano Barbosa Vasconcelos; Marília de Carvalho Lima; Arnaldo de França Caldas Júnior (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the barriers to access and oral health care faced by children and adolescents with Cerebral Palsy (CP) according to their motor impairment through the perception of caregivers. Material and Methods: A case series study was carried out at three health institutions in Pernambuco, Brazil. The study sample consisted of 94 caregivers of 5-to-18-year-old patients with CP, according to GMFCS (The Gross Motor Function Classification System). Data were collected using a semi-structured form to evaluate the barriers to access and analyzed statistically by the chi-square and Fisher exact tests, adopting a 5% level of significance. In addition, binary logistic regression was performed to determine the weight of the variables in explaining the outcome variable. Results: There were major difficulties involving transportation (p=0.04) and structural accessibility to dental services (p<0.01) among children and adolescents with severe CP. In addition, the more severe the CP, the greater the difficulty of accessibility (OR=4.09,) and the lower the income (OR=8.80), the greater the motor impairment. Conclusion: Despite the availability of access to dental services, low-income families have more severe CP patients, contributing to the daily difficulties already faced by them in oral health care.